On the nature of acquiescence to police authority: A commentary on Hamm et al. (2022) - Jackson, Jonathan (Legal and criminological psychology, 2022)
The excellent target article raises much food for thought. In this commentary we first discuss what is included in their proposed category of ‘positive evaluations and responses to police assertions of power to attempt social influence’. We then consider some of the implications of the concentric diagram for our understanding of police authority and power.